Superconductivity and antiferromagnetism in quasi-one-dimensional organic conductors: Spin Models - Dupuis, N.; Bourbonnais, C.; Nickel, J.C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We review the current understanding of superconductivity in the quasi-one-dimensional organic conductors of the Bechgaard and Fabre salt families. We discuss the interplay between superconductivity, antiferromagnetism, and charge-density-wave fluctuations. The connection to recent experimental observations supporting unconventional pairing and the possibility of a triplet–spin order parameter for the superconducting phase is also presented.